The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1999
DOI: 10.1515/hf.1999.093
|View full text |Cite
|
Sign up to set email alerts
|

Production of Polygalacturonase and Increase of Longitudinal Gas Permeability in Southern Pine by Brown-Rot and White-Rot Fungi

Abstract: Hydrolysis of bordered and pinoid pits may be a key event during colonization of wood by decay fungi. Although pits are numerous, studies of pectin-hydrolyzing enzymes in wood decay fungi are scarce, probably because of the relatively low content (less than 4 %) of pectin in wood and because of the primary focus on understanding the degradation of lignified components. Endopolygalacturonase (endo-PG) activity was estimated by cup-plate assay and viscosity reduction of pectin from liquid cultures of fifteen bro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(10 citation statements)
references
References 14 publications
1
9
0
Order By: Relevance
“…In contrast, degradation of piceoid pit membranes in P. abies was more localised and was restricted to cells near the outer surfaces of the specimens. Previous studies have demonstrated that most brown-and white-rot fungi have the capacity to hydrolyse the pectin in pit membranes during incipient decay, which facilitates colonisation (Cowling 1961;Wilcox 1968;Green and Clausen 1999;Schwarze and Landmesser 2000;Schwarze et al 2004).…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, degradation of piceoid pit membranes in P. abies was more localised and was restricted to cells near the outer surfaces of the specimens. Previous studies have demonstrated that most brown-and white-rot fungi have the capacity to hydrolyse the pectin in pit membranes during incipient decay, which facilitates colonisation (Cowling 1961;Wilcox 1968;Green and Clausen 1999;Schwarze and Landmesser 2000;Schwarze et al 2004).…”
Section: Resultsmentioning
confidence: 99%
“…In a more recent study, the same authors showed that, while grapevine summer pruning leads to the production of tylose, winter pruning essentially leads to the secretion of gels that have pectin as a major component (Sun et al 2008). Pectin is a perfect substrate for decomposition by fungi (Green et al 1996;Green and Clausen 1999). Several esca-associated wood-rot fungi, e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Due to its unique multiple chemical natures, it has been receiving much attention for its various ecological qualities, such as: (i) bioremediation of a wide variety of organic pollutants (2) with lignin biodegradation systems (3-7); (ii) inactivation of copper-containing wood preservatives by wood-rotting fungi (8,9); (iii) detoxification of aluminum toxicity in Al-resistant buckwheat (10); (iv) crop damage caused by oxalic acid-producing phytopathogens (11,12); (v) the biofertilizer effect of ectomycorrhizal fungi (13,14); and (vi) being an electron source for nitrogen fixation in symbiotic rhizobia in a legume plant (15). In addition, oxalic acid is known as the general physiological trait that most brown-rot basidiomycetes, including Fomitopsis palustris, accumulate oxalic acid at greater concentrations in culture fluid, whereas white-rot ones do not because they metabolize and͞or decompose oxalic acid by various mechanisms (16)(17)(18)(19). Nevertheless, the whiterots were observed to accumulate Ca-oxalate during wood decay processes (20).…”
mentioning
confidence: 99%